Perspective taking in judgment of relative direction tasks. - Geva, Danit; Henik, Avishai (Memory & Cognition, 2019)
Mental rotation and visual-spatial perspective taking (VSPT) are two visual-spatial abilities that are highly correlated. Judgment of relative direction (JRD) tasks are commonly used to examine VSPT in conjunction with mental rotation. Moreover, in many studies the task involves switching from an imagined perspective to a sensorimotor perspective at the response phase. The current study employed a JRD task that enabled examination of mental rotation, perspective taking, and perspective switching, separately. In two experiments we found that both perspective taking and perspective switching affected accuracy and response time (RT). Namely, trials with a perspective change larger than 90° (that required perspective taking) were harder than trials with a change smaller than 90° (that required mental rotation), and so were trials that required switching from an imagined perspective to a sensorimotor perspective. Importantly, we suggest that VSPT and mental rotation are dissociable.